PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Farmasi yang Terdaftar di BEI Periode 2013-2016) - NEVRIZKA AUDYA PERMATA (Jurnal Ilmiah Mahasiswa FEB, 2018)
Abstract: This research is aimed to find out the influence of profitability (Returnon Equity), capital structure (Debt to Equity Ratio), and Firm’s Size (SIZE) onCorporate Value (Price to Book Value). Independent variable including ROE, DER,and SIZE and dependent variable including PBV. Methods used for data collectionis saturated sampling technique in pharmaceutical companies listed on the IDXduring 2013-2016. Total sample used as many as 9 companies. Methods used for data analysis is multiple linear regression test. The results of this research indicate that the variable ROE and SIZE have positive significant influence on PBV, while the variable DER has no significant influence on PBV. Keywords: Return on Equity (ROE), Debt to Equity Ratio (DER), SIZE, Priceto Book Value (PBV).